Atypical multifocal Dravet syndrome lacks generalized seizures and may show later cognitive decline. (25th October 2013) - Kim, Young Ok; Bellows, Susannah; McMahon, Jacinta M; Iona, Xenia; Damiano, John; Dibbens, Leanne; Kelley, Kent; Gill, Deepak; Cross, J Helen; Berkovic, Samuel F; Scheffer, Ingrid E
<x xml:space="preserve">Abstract</x> Aim To show that atypical multifocal Dravet syndrome is a recognizable, electroclinical syndrome associated with sodium channel gene (SCN1A) mutations that readily escapes diagnosis owing to later cognitive decline and tonic seizures. Method Eight patients underwent electroclinical characterization. SCN1A was sequenced and copy number variations sought by multiplex ligation‐dependent probe amplification. Results All patients were female (age range at assessment 5–26y) with median seizure onset at 6.5 months (range 4–19mo). The initial seizure was brief in seven and status epilepticus only occurred in one; three were febrile. Focal seizures occurred in four patients and bilateral convulsion in the other four. All patients developed multiple focal seizure types and bilateral convulsions, with seizure clusters in six. The most common focal seizure semiology (six out of eight) comprised unilateral clonic activity. Five also had focal or asymmetric tonic seizures. Rare or transient myoclonic seizures occurred in six individuals, often triggered by specific antiepileptic drugs. Developmental slowing occurred in all: six between 3 years and 8 years, and two around 1 year 6 months. Cognitive outcome varied from severe to mild intellectual disability. Multifocal epileptiform discharges were seen on electroencephalography. Seven out of eight patients had SCN1A mutations. Interpretation Atypical, multifocal Dravet syndrome with SCN1A mutations may not be recognized because of later cognitive decline and frequent tonic seizures.